Financial Performance Behavioral in the Company Life Cycle - Sumail, La Ode; Akob, Rezki Arianty (University of Merdeka Malang, 2021)
The diversity of financial performance behavior occurs in companies listed on the Indonesian capital market. This study aims to investigate and analyze the behavior of financial performance in the company's life cycle at various stages, including early expansion, late expansion, maturity , and decline. The object of this research is a manufacturing company registered in the Indonesian capital market at least ten years after the IPO and has a complete financial performance report. The regression analysis results prove that the behavior of financial performance varies in each stage of the company's life. i.e., dividend behavior, retained earnings behavior (Retained Earnings to Total Equity), profitability behavior, financial leverage behavior, risk behavior, Cash flows from investment (CFI) behavior. Cash flows from operations (CFO) and behavior Cash flows from financial (CFF). JEL: G14, G23, G41